[Job satisfaction measurement scales: a critical review] - Faraci, Palmira; Magnano, Paola; Valenti, Giusy Danila (Giornale Italiano di Medicina del Lavoro ed Ergonomia, 2025)
Introduction. Job satisfaction is very significant in the field studies of occupational wellbeing. A vast number of published studies have suggested a link between job satisfaction levels and both organizational behavior and physical and mental health. The detection of effective intervention strategies needs an accurate assessment. Therefore, the problem of choosing precise measurement instruments takes place.Objectives. The present paper is aimed to provide a framework about the characteristics of available measures of job satisfaction, in its globality, as a unit, as well as in its component parts. Methods. A critical review was conducted, systematically describing instruments as classified into single-item scales, one-dimensional scales, and multidimensional scales.Psychometric qualities and structural features are indicated for each presented measure.Results. From literature-based analysis a large amount of existing instruments emerged, with some differences referring to their validity, reliability, and practical usefulness. Overall, we presented 23 self-report scales, 7 of which are addressed to a global evaluation, whereas 14 are multidimensional. Some scales are specifically developed to be used in healthcare, medical, and nursing areas.Conclusions. An accurate method for evaluation is at the bottom of the development of effective programs for the prevention of work related risk factors. This overview might be helpful as a guidance tool for determining if an instrument is suitable for a specific purpose.